The Talmud : a biography - Wimpfheimer, Barry S. (Lives of great religious books., 2018)
The life and times of an enduring work of Jewish spiritualityThe Babylonian Talmud, a postbiblical Jewish text that is part scripture and part commentary, is an unlikely bestseller. Written in a hybrid of Hebrew and Aramaic, it is often ambiguous to the point of incomprehension, and its subject matter reflects a narrow scholasticism that should hardly have broad appeal. Yet the Talmud has remained in print for centuries and is more popular today than ever. Barry Scott Wimpfheimer tells the remarkable story of this ancient Jewish book and explains why it has endured for almost two millennia. Providing a concise biography of this quintessential work of rabbinic Judaism, Wimpfheimer takes readers from the Talmud's prehistory in biblical and second-temple Judaism to its present-day use as a source of religious ideology, a model of different modes of rationality, and a totem of cultural identity. He describes the book's origins and structure, its centrality to Jewish law, its mixed reception history, and its golden renaissance in modernity. He explains why reading the Talmud can feel like being swept up in a river or lost in a maze, and why the Talmud has come to be venerated--but also excoriated and maligned--in the centuries since it first appeared. An incomparable introduction to a work of literature that has lived a full and varied life, this accessible book shows why the Talmud is at once a received source of traditional teachings, a touchstone of cultural authority, and a powerful symbol of Jewishness for both supporters and critics.